The Effect of Digital Marketing and Brand Image on MSME Performance MOI Kelapa Gading Square Moderated Product Quality - Kustiadi Basuki; Annisa Nur Husni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to recommend strategies for the performance of MSMEs. The research method used is using a quantitative approach. Descriptive quantitative research method with the presentation of numbers starting from data collection, data interpretation and presentation of the results of the numbers. The results of this study prove that digital marketing has a positive and significant influence on performance in MSMEs and product quality has a positive and significant impact on brand image which is moderated by performance in MSMEs.